ANALYSIS AND OPTIMIZATION OF AUTOMATED POWER DISTRIBUTION WITHIN NIGERIA - Ofualagba, Godswill; Ejofodomi, O'tega (International Journal of Applied Power Engineering (IJAPE))
Nigeria currently generates approximately 81,122 MWH (or 3,380 MWH/H) of electricity for national consumption, which is far less than the daily electricity demand of  the country, leading to a need for allotted power distribution within the country. A power optimization software owned and patented by RACETT NIGERIA LTD. was used to perform automated distribution of electricity from the National Grid for October 1, 2019, with priority given to the peak demand period of 8:00 p.m. -11: 00 p.m. The distribution results show that Nigeria is currently able to provide 4 hours of electricity across the nation from 8:00 p.m. - 12:00 a.m. Eight (8) states received electricity for only 4 hours of the day, while some states like Lagos State received as much as 24 hours.  The percentage grid allocation to the distribution companies needs to be revised to improve even distribution of electricity across the nation, and transmission and distribution losses need to be drastically reduced. Further analysis revealed that Nigeria presently needs to generate 240,000 MWH (or 19 , 583 MWH/H) of electricity in order to provide 24 hours of electricity to every state across the nation.